Observer-based controller design of time-delay systems with an interval time-varying delay - Thuan, Mai Viet; Phat, Vu Ngoc; Trinh, Hieu (Zielona Góra: Uniwersytet Zielonogórski)
This paper considers the problem of designing an observer-based output feedback controller to exponentially stabilize a class of linear systems with an interval time-varying delay in the state vector. The delay is assumed to vary within an interval with known lower and upper bounds.
Keywords: observer-based feedback control; interval time-varying delay; linear matrix inequalities; Lyapunov-Krasovskii functionals; exponential stability